Towards a revival of analytical philosophy of history : around Paul A. Roth's vision of historical sciences - Brzechczyn, Krzysztof, 1963- (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2018)
Towards a Revival of Analytical Philosophy of History: Around Paul A. Roth's Vision of Historical Sciences presents the state of the art in the philosophy of history. The purpose of this book is to discuss the revival of analytical philosophy of history proposed by Paul A. Roth, a world-known analytical philosopher of the social sciences and the humanities. The first four papers outline the reasons for the decline of philosophy of history, its present phase of development, and its possible future. The other authors discuss important questions of this field of research including: the ontological status of the past, the epistemological assumptions of historical research, the explanatory dimensions of the narrative. In the last group of papers, the authors apply some of Roth's theoretical ideas within their own fields of research. Contributors are: Krzysztof Brzechczyn, Nancy D. Campbell, Serge Grigoriev, Géza Kállay, Piotr Kowalewski, Jouni-Matti Kuukkanen, Chris Lorenz, Herman Paul, Dawid Rogacz, Paul A. Roth, Laura Stark, Stephen Turner, Rafał Paweł Wierzchosławski, and Eugen Zeleňák.